Resource Use and Costs Associated to the Initial Phase of Treatment for Patients with Colorectal Cancer Receiving Post-Surgery Chemotherapy: A Cost Analysis from a Healthcare Perspective - Mina Nejati; Moaven Razavi; Iraj Harirchi; Marzieh Zanganeh; Gholamreza Salari; Seyed Mosa Tabatabaee (Tehran University of Medical Sciences, 2021)
Background: To estimate the resource use and costs associated to the initial phase of treatment for colorectal cancer in Iran. Methods: A retrospective study was conducted using routinely collected data within Electronic Health Records System (SEPAS), a national database representing public hospitals in Iran between March 20, 2016 and March 19, 2017. Primary end points included healthcare resource use, direct medical and non-medical costs of care in the 12-month study period. Results: The study population included 657 patients with colorectal cancer who underwent surgery and the follow-up chemotherapy. We estimated a total direct cost of $21,407 per patient. The results indicated that direct medical costs were primarily driven by inpatient hospital care, followed by surgery, chemotherapy, and diagnostic services. Conclusion: The initial 12-month of treatment for colorectal cancer, including surgery and the follow-up chemotherapy, is resource intensive. The total direct costs associated to the disease are remarkable, with Inpatient hospital services being the main contributor followed by surgery and chemotherapy.